Pengayaan Pembelajaran Reproduksi Manusia Dalam Pandangan Islam : Studi Kasus Di Kelas XI SMA Negeri 1 Kedungadem Bojonegoro Tahun 2018-2019 - Abdur Rohim; Sri Susanti Tjahja Dini (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
This research takes the theme of enrichment of human reproduction learning in the view of Islam in SMA Negeri 1 Kedungadem Bojonegoro. The reason for this research is that the phenomenon of the high number of social pathology in the Bojonegoro Kedungdalem area. In the last 3 years vulnerable, from 2016 to 2018 there were many cases of abortion and cases of pregnancy outside marriage in Kedungadem District. In 2016 there were 2 cases of pregnancy out of wedlock, in 2017 there was 1 case of pregnancy out of wedlock, whereas in 2018 there was an increase in which there was 1 case of abortion and 3 cases of pregnancy out of wedlock. This research was designed with a research and development approach, in accordance with the research instructions, then the data was collected and analyzed accordingly in the theoretical study in Chapter II so that the descriptive data was revealed and could find the meaning of the phenomena that occur in research naturally. The results of the analysis of this study can be concluded 1. Human reproduction learning in general in the material of human reproduction has been carried out well by biology teachers because it has fulfilled its components, namely, there are core competencies, basic competencies, indicators and learning objectives. 2. Learning of human reproduction in the view of Islam in biology subjects has not been included, to facilitate the teacher in the implementation we made a learning module and learning PowerPoint that we pack in the form of a CD as attached. 3. The results of the enrichment of human reproduction learning in the Islamic perspective, enrichment of learning according to stakeholders of SMA Negeri 1 Kedungadem Bojonegoro is considered important, necessary, and in accordance with students in SMA Negeri 1 Kedungadem Bojonegoro